Prune-belly syndrome - Yenny Yenny; Kusuma P. A; Damanik M. P. (Indonesian Pediatric Society Publishing House, 2009)
Prune-belly syndrome, also known as Eagle-Barret syndrome, is a congenital anomaly comprising three clinical findings: deficient abdominal musculature, urinary tract anomalies, and bilateral cryptorchidism. Other clinical findings involving respiratory, skeletal, digestion and cardiovascular system may also accompany the syndrome. The incidence is approximately 1 : 30,000 to 40,000 live births and 95% of cases occur in boys. Pulmonary hypoplasia and kidney failure are important prognostic factors that contribute to 60% of mortality rate. Treatment includes surgical correction of the abdominal wall and urinary tract, orchidopexy and other supportive managements.l-4 We report 4 cases on typical Prune-belly syndrome, together with other clinical variants.